Design, simulation and fabrication of optical filters for narrow band imaging in endoscopic capsules - Silva, M. F. (2011)
This paper presents the design, simulation and fabrication of two optical filters that could be integrated in endoscopic capsules (EC) to perform narrow band imaging (NBI) analysis. The thin-film optical filters were designed for two specific spectral regions (blue, centered at 415 nm, and green, centered at 540 nm) and will be placed on top of current EC white light emitting diodes (LEDs). The filters are composed by 7 thin-film layers of titanium dioxide (TiO2) and silicon dioxide (SiO2) and will be deposited using RF-sputtering technique. The integration of NBI functions in EC represents an important clinical and technological advance, since it will improve the EC diagnostic functions, e.g. enhanced visibility of capillaries and veins for the diagnosis of dysplasia, as a complement to the current capsule vision based in white light.